How to reduce energy and water consumption in the preparation of raw materials for ceramic tile manufacturing: Dry versus wet route. (1st December 2017) - Mezquita, A.; Monfort, E.; Ferrer, S.; Gabaldón-Estevan, D.
Abstract: Dry and wet routes in the ceramic tile manufacturing process refer to two different technologies for preparing the raw materials for the forming stage. Both result in a granulated solid ready for use in the pressing stage, but with different characteristics. The dry route was the first to be developed. As quality standards and tile sizes increased, the wet route was developed and introduced successfully into the manufacturing process. Since 1990, the wet route has been the most used around the world to prepare ceramic tile body raw materials. The powder produced by the wet route has finer particles and higher flowability, which has allowed the production of higher quality ceramic tiles of larger sizes. However, the process uses more energy and water and, consequently, is more costly in both economic and environmental terms. New developments in dry milling and granulation systems combined with the growing awareness of environmental impacts and European Union energy policy, and successful uses of the dry route in some important tile producer countries (especially Brazil), are leading to a reconsideration of the tile production processes. In the current context, implementation of the dry route is being considered an interesting alternative for the production of ceramic tiles with lower environmental costs. This has resulted in a significant number of studies of the technology from applied research centres and machinery producers. The present paper provides an up to date technical and environmental comparison of the dry and wet routes, based on the most recent advances, to add to the debate on the use of the dry route to produce high quality ceramic tiles. Highlights: Dry route has been seen as an interesting alternative to produce ceramic tiles. New developments in dry milling and granulation systems. Successful use of the dry route in some important producer countries. Environmental issues affecting the ceramic tile industry are gaining momentum.